The Effect of the Clenbuterol—β2-Adrenergic Receptor Agonist on the Peripheral Blood Mononuclear Cells Proliferation, Phenotype, Functions, and Reactive Oxygen Species Production in Race Horses In Vitro - Olga Witkowska-Piłaszewicz; Rafał Pingwara; Jarosław Szczepaniak; Anna Winnicka (Cells, 2021)
Clenbuterol, the β2-adrenoceptor agonist, is gaining growing popularity because of its effects on weight loss (i.e., chemical liposuction). It is also popular in bodybuilding and professional sports, due to its effects that are similar to anabolic steroids. However, it is prohibited by anti-doping control. On the other hand, it is suggested that clenbuterol can inhibit the inflammatory process. The cells from 14 untrained and 14 well-trained race horses were collected after acute exercise and cultured with clenbuterol. The expressions of CD4, CD8, FoxP3, CD14, MHCII, and CD5 in PBMC, and reactive oxygen species (ROS) production, as well as cell proliferation, were evaluated by flow cytometry. In addition, IL-1β, IL-4, IL-6, IL-10, IL-17, INF-γ and TNF-α concentrations were evaluated by ELISA. β2-adrenoceptor stimulation leads to enhanced anti-inflammatory properties in well-trained horses, as do low doses in untrained animals. In contrast, higher clenbuterol doses create a pro-inflammatory environment in inexperienced horses. In conclusion, β2-adrenoceptor stimulation leads to a biphasic response. In addition, the immune cells are more sensitive to drug abuse in inexperienced individuals under physical training.